The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1007/s11661-001-0091-0
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation as a strength probe—a study on the hardness dependence of indent size for fine-grained and coarse-grained ferritic steel

Abstract: A nanoindentation hardness testing system, including an atomic-force microscope (AFM)-based nanoindentation tester and a calibration method using electrolytically polished single-crystal metals as references, was proposed. This was applied to a study of the mechanical properties of fine-grained ferritic steel (grain size of 1.2 m) and coarse-grained ferritic steel (30 m). An empirical function giving the macroscopic hardness for all four reference metals from the nanoindentation force curves was established. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 16 publications
(15 reference statements)
0
21
0
Order By: Relevance
“…They investigated the hardness dependence of indent size by introducing a converted Vickers hardness. 12) They also revealed quantitatively the contribution of dislocation, solutes, block boundary and cementite to hardness in tempered martensitic steels used at room temperature by means of the same method. 13) By using the nanoindentation technique, Komazaki et al 14) reported that hardness inside lath grain decreases at the primary stage of creep deformation in 9Cr-0.5Mo-1.8W-VNb steel.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…They investigated the hardness dependence of indent size by introducing a converted Vickers hardness. 12) They also revealed quantitatively the contribution of dislocation, solutes, block boundary and cementite to hardness in tempered martensitic steels used at room temperature by means of the same method. 13) By using the nanoindentation technique, Komazaki et al 14) reported that hardness inside lath grain decreases at the primary stage of creep deformation in 9Cr-0.5Mo-1.8W-VNb steel.…”
Section: Introductionmentioning
confidence: 91%
“…Miyahara et al 12) revealed the contribution of grain boundary to hardness in fine-grained ferritic steel by using a nanoindentation hardness system. They investigated the hardness dependence of indent size by introducing a converted Vickers hardness.…”
Section: Introductionmentioning
confidence: 99%
“…An AFM ultra micro-hardness tester with special levers developed by NIMS was utilized for testing the hardness at the nanoscale level [10][11][12][13]. In this study, two types of special levers with apical angles of 60 o and 115 o were used for the triangular pyramidal indenter.…”
Section: Methodsmentioning
confidence: 99%
“…An indentation test is one of the most common techniques used to extract the local material properties at the nano-, sub-micron-, and micron-scale [10][11][12]. In particular, nanoindentation combined with atomic force microscopy (AFM) is useful for evaluating the hardness of a specific nanoscale site in a material having complex microstructures, because an in-situ AFM image enables the accurate setting of a Berkovich indenter with a triangular pyramidal shape at the desired site [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation